The Gender Performances of Margaret Atwood’s Aunt Lydia in "The Testaments" - Weiss, Jordyn (Journal of Literary Studies)
This article examines the different gender performances that are demonstrated by three versions of the character Aunt Lydia: first, the Aunt Lydia of the novel version of The Handmaid’s Tale (Atwood, 2010); second, the television version of the same character for the Hulu series, The Handmaid’s Tale; and third, the Aunt Lydia that Margaret Atwood focuses on in her latest novel, The Testaments (2019). The research is primarily informed by Judith Butler and her various works on the subject of gender performativity. The Handmaid’s Tale novel’s Aunt Lydia performs the gender role of Gileadean Aunt. In the TV adaptation of the novel, Lydia continues her performance of the Aunt gender role, but audiences are also provided with a glimpse into Lydia’s pre-Gileadean gender performances. Finally, in The Testaments, Lydia performs multiple gender roles: that of the Aunt, as the other versions of her character do, and, in private, that of a woman who aims to restore Gileadean women’s freedom.